The effect of externally generated loading on predictive grip force modulation. - WITNEY, ALICE (My University, 2007)
A characteristic of skilled movement is the ability of the CNS to predict the consequences of motor commands. When we lift an object there is an anticipatory increase in grip force that prevents a grasped object from slipping. When an object is pulled from our grasp by an external force, a reflexive modulation in grip force prevents slippage. Here we examine how external perturbations to a grasped object influence anticipatory grip force during object manipulation using a bimanual task, with each hand holding a computer-controlled object. Subjects were instructed to maintain the position of the object held in the right hand. Loading was applied to this restrained object: either self-generated by the action of their left hand or externally generated by a motor. The magnitude of the grip force response to self-generated loading increased after the object was loaded, and the latency of this response remained predictive of load force. This implies that external and self-generated loading increase the anticipatory grip force response. Unlinked trials, where the subject's moved their left hand but no loading was generated on the right-hand object were used to assess the presence of purely predictive control of grip force. External loading soon after self-generated loading maintained an existing predictive response once the linkage between the subject's action and object loading had been removed. However, external loading had no influence as the existing prediction decays. Therefore, the predictive grip force response during object manipulation can be significantly modified by object loading from an external source.
PUBLISHED
Keywords: Predictive models; Grip force; Neuroscience